Pengaruh Pemberian Madu dalam Meningkatkan Status Gizi pada Anak Usia Toddler - Anita Wulan Ningrum; Surati Ningsih (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2022)
Health conditions in infants could be affected by appetite, sleep quality, weight, and haemoglobin. In the Sukoharjo District Hamlet, there were approximately 6 of the 20 toddler children with nutritional status problems or children with the Red Bottom Line (BGM). One of the causes of malnutrition in children was a decrease in appetite. This study was to describe the management of honey to improve nutritional status in toddler age children. The type of research used was descriptive qualitative with a case study research approach. The data collection technique was taken by purposive sampling using inclusion criteria aged 1-3 years and toddlers with BB below BB ideal calculated by (2n+8). Child assessment data had difficulty eating, difficulty eating vegetables and fruit. Physical examination: non-luminous hair, dry lip mucosa, sunken eyelids, skin elastic turgor, no folds under the skin. BB measurement results below BB are ideal. Nursing diagnosis: imbalance of nutrients less than the body's needs b.d lack of food intake, the action taken is giving honey. The results of this study that after giving honey for 2 weeks there was an increase in appetite and an increase in BB in children (60%). There is an effect of giving honey with an increase in nutritional status in toddler age children.